Direct LC-MS/MS Analysis of Extra- and Intracellular Glycerophosphoinositol in Model Cancer Cell Lines - Campos, Ana Margarida; Nuzzo, Genoveffa; Varone, Alessia; Italiani, Paola; Boraschi, Diana; Corda, Daniela; Fontana, Angelo (Frontiers in Immunology, 2021)
Glycerophosphoinositols (GPIs) are water-soluble bioactive phospholipid derivatives of increasing interest as intracellular and paracrine mediators of eukaryotic cell functions. The most representative compound of the family is glycerophosphoinositol (GroPIns), a ubiquitous component of mammalian cells that participates in cell proliferation, cell survival and cell response to stimuli. Levels and activity of this compound vary among cell types and deciphering these functions requires accurate measurements in in vitro and in vivo models. The conventional approaches for the analysis of GroPIns pose several issues in terms of sensitivity and product resolution, especially when the product is in the extracellular milieu. Here we present an UPLC-MS study for the quantitative analysis of this lipid derivative in cells and, for the first time, culture supernatants. The method is based on a solid-phase extraction that allows for fast desalting and analyte concentration. The robustness of the procedure was tested on the simultaneous measurements of intra- and extracellular levels of GroPIns in a number of human cell lines where it has been shown that the non-transformed cells are characterized by high extracellular level of GroPIns, whereas the tumor cells tended to have higher intracellular levels.